Simplified numerical simulation to obtain heat transfer correlations for stirred yoghurt in a plate heat exchanger - Afonso, I. M. (2008)
In the present work a numerical investigation was conducted in order to obtain correlations for the determination of convective heat transfer coefficients of stirred yoghurt during the cooling stage in a plate heat exchanger, taking into account its rheological features. The main simplification in the simulation method was the assumption of bi-dimensional flow in a flat plate geometry. By combining the resulting theoretical equations for a flat geometry with the geometric parameters usually defined for corrugated parameters (aspect ratio, hydraulic diameter), correlations for the convective coefficients were obtained that compare well to the experimental ones. This simplified and much faster simulation methodology proved to be appropriate for highly viscous, low Reynolds number flow situations.